The Shock of the New: The power and perception of neologisms. Issue 2 (21st December 2015) - Elmes, Simon
Abstract : It was the late Robert Hughes's remarkable TV series and book on modern art, The Shock of the New, first seen in the early 1980s, that with its title so deftly captured the both the excitement and the puzzlement to the beholder of creative novelty and innovation. And it is in many ways a self-fulfilling phrase, since epigrammatic, yet meaning-laden titles and names are the stuff of the broadcast programmer and the namer of new products. The new can indeed be shocking to the beholder, and Hughes's title says it in a sharp, monosyllabic manner whose five-word cadence has both balance and rhythm. Shuffle the words – or render them in a different grammatical format ('novelty shocks', for example) – and it falls apart. Words applied to new things and events matter, because they need to be repeated and, the makers hope, be talked about; resonance and repeatability are important to original things being launched on an unsuspecting public.